2016
DOI: 10.6000/1927-5129.2016.12.08
|View full text |Cite
|
Sign up to set email alerts
|

Combining Ability Estimates for Yield and Fiber Quality Parameters in Gossypium Hirsutum L. Hybrids

Abstract: General and specific combining ability effects were discriminated in different parents and offspring to isolate the potential of genotypes used in diallel system to attain the genetic inheritance pattern ascertain with the nature of gene action. A six-by-six, hirsutum diallel excluding reciprocals, was analyzed for general and specific combining ability estimates and components of genetic variation to investigate the genetic retrospect and inheritance pattern of eleven quantitative and fiber quality characters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…The results regarding heterotic effects in F1 and F2 generation shown similar trend except GOT%. Several previous researches like Kaushik andSastry (2011), Patil et al (2011), Kumbhar et al (2016) observed the significant differences in F1 and F2 hybrids of upland cotton. www.pjbt.org…”
Section: Analysis Of Variancementioning
confidence: 88%
“…The results regarding heterotic effects in F1 and F2 generation shown similar trend except GOT%. Several previous researches like Kaushik andSastry (2011), Patil et al (2011), Kumbhar et al (2016) observed the significant differences in F1 and F2 hybrids of upland cotton. www.pjbt.org…”
Section: Analysis Of Variancementioning
confidence: 88%
“…Imran et al (2012), Kumar et al (2013), Simon et al (2013) and Raza et al (2013) came to the same conclusion. However, Memon et al (2016) found that the gca variance was larger than that of sca, and the rank order for gca's of the parents differed from F1 to F2 …”
Section: Genetic Parametersmentioning
confidence: 90%
“…Diallel analysis, as developed by Hayman (1954 and1958), Jinks (1956) and Jinks & Hayman (1953), provides full information to identify superior parents and crosses for different traits. Several researchers (Luckett, 1989;Khan et al 1995;Iqbal & Khan, 1996;Esmail et al, 1999;Mukhtar et al 2000;Nadeem & Azhar, 2004;Basal & Turgut, 2005;Mohamed et al 2009;Imran et al 2012;Kumar et al 2013;Raza et al 2013;Simon et al 2013;Soomro et al 2006;Waqar et al 2015 andMemon et al, 2016) pointed to the importance of genetic studies of the materials before selecting the desirable plant. Azhar & Khan (2005), Abbas et al (2008), Abd El-Bary et al (2008), Zangi et al (2009), Palv (2009 and Darweesh (2010) reported that GCA effects were highly significant for number of bolls, seed cotton yield and lint percentage.…”
Section: Introductionmentioning
confidence: 99%
“…Additive gene action with higher GCA estimates and non-additive gene action with higher SCA estimates have potential role in the identification and selection of superior lines. 2 Due to the importance and demand of cotton it is necessary to develop cotton varieties with high yield potential and fiber qualities. For this purpose it is necessarily to study the inheritance pattern of genes for various yield and fiber quality contributing traits which are helpful for the genetic improvement of available germplasm.…”
Section: Introductionmentioning
confidence: 99%